2019
DOI: 10.1371/journal.pone.0211928
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of tooth extraction-triggered bisphosphonate-related osteonecrosis of the jaws with basic fibroblast growth factor: An experimental study in rats

Abstract: Osteonecrosis of the jaw induced by administration of bisphosphonates (BPs), BP-related osteonecrosis (BRONJ), typically develops after tooth extraction and is medically challenging. As BPs inhibit oral mucosal cell growth, we hypothesized that suppression of the wound healing-inhibiting effects could prevent BRONJ onset after tooth extraction. Since basic fibroblast growth factor (bFGF) promotes wound healing, but has a short half-life, we examined whether the initiation of BRONJ could be prevented by applyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Mucosal/gingival integrity and healing are necessary to protect alveolar bone and prevent bacterial colonization. Although mucosal ulceration‐triggered MRONJ is rare (Chang et al, 2018), bisphosphonates have shown several adverse effects on soft tissue (Imada et al, 2019; Kim et al, 2017; Kobayashi et al, 2010; Kozutsumi et al, 2022; Kumar & Sinha, 2013; Reid & Cornish, 2011; Sun et al, 2016; Tamari et al, 2019; Yamashita et al, 2011). In an animal study (Kim et al, 2017), the authors found a higher level of the pro‐inflammatory cytokine IL‐36α and a lower level of collagen in murine BRONJ‐like lesions.…”
Section: Possible Pathophysiological Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucosal/gingival integrity and healing are necessary to protect alveolar bone and prevent bacterial colonization. Although mucosal ulceration‐triggered MRONJ is rare (Chang et al, 2018), bisphosphonates have shown several adverse effects on soft tissue (Imada et al, 2019; Kim et al, 2017; Kobayashi et al, 2010; Kozutsumi et al, 2022; Kumar & Sinha, 2013; Reid & Cornish, 2011; Sun et al, 2016; Tamari et al, 2019; Yamashita et al, 2011). In an animal study (Kim et al, 2017), the authors found a higher level of the pro‐inflammatory cytokine IL‐36α and a lower level of collagen in murine BRONJ‐like lesions.…”
Section: Possible Pathophysiological Mechanismsmentioning
confidence: 99%
“…MRONJ has been demonstrated to worsen both quality of life (QoL) and oral health‐related QoL (Bensi et al, 2021; Miksad et al, 2011; Tenore et al, 2020), which strongly suggests that clarification of the pathophysiology and establishment of a treatment strategy are imperative. However, establishment of a comprehensive clinical practice guideline and/or of suggestions for treating MRONJ has been challenging (Kawahara, Kuroshima, & Sawase, 2021; Khan et al, 2015; Miksad et al, 2011; Ruggiero et al, 2022; Yarom et al, 2019), due to the low frequency of MRONJ in clinical situations and no clarification of the definitive pathophysiology and histopathology/immunopathology of MRONJ, although good basic science research regarding MRONJ has been conducted (Abtahi, Agholme, Sandberg, & Aspenberg, 2013; Adachi et al, 2020; Aghaloo et al, 2011; Aghaloo et al, 2014; Aguirre et al, 2010; Aguirre et al, 2012; Aguirre, Castillo, & Kimmel, 2021a, 2021b; Akita et al, 2018; Bi et al, 2010; Biguetti et al, 2019; Castillo et al, 2021; de Molon et al, 2014; de Molon et al, 2015; Elsayed et al, 2020; Ervolino et al, 2019; Gao et al, 2021; Gkouveris et al, 2019; Hadaya et al, 2019; Hayano et al, 2020; Hikita, Miyazawa, Tabuchi, Kimura, & Goto, 2009; Hokugo et al, 2010; Hokugo et al, 2019; Hokugo, Sun, Park, McKenna, & Nishimura, 2013; Howie et al, 2015; Imada et al, 2019; Inoue, Matsumoto, Nakajima, Kuroshima, & Sawase, 2021; Kaibuchi, Iwata, Yamato, Okano, & Ando, 2016; Kang et al, 2013; Kikuiri et al, 2010; Kim et al, 2017; Kim et al, 2018; Kobayashi et al, 2010; Kozutsumi et al, 2022; Kuroshima et al, 2018a, 2018b; Kuroshima et al, 2019; Kuroshima et al, 2021; Kuroshima, Al‐Salihi, & Yamashita,…”
Section: Introductionmentioning
confidence: 99%
“…Platelet growth factor mixture (PGFM) and basic fibroblast growth factor (bFGF) are well-known growth factors. They have been used clinically in various surgical treatments for soft and hard tissues, such as cosmetic surgery, orthopedics, and maxillofacial surgery [ [23] , [24] , [25] ]. However, the free form of these growth factors simply added to iGel will disappear immediately.…”
Section: Introductionmentioning
confidence: 99%
“…With all these advantages of the curcumin, nanoparticles could be directly injected to the patients with any form of injection to reduce the importance of the local drug. [23][24][25] A natural plant of the curcumin polyphenol compounds, extracted from the turmeric plants which are easily available in Asian regions, is mainly used for pharmacological purposes. The curcumin shows excellent antioxidant property, such as anti-inflammatory, antifungus, and antitumor, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…With all these advantages of the curcumin, nanoparticles could be directly injected to the patients with any form of injection to reduce the importance of the local drug. 23 - 25 …”
Section: Introductionmentioning
confidence: 99%